Muhammad Iqbal: Islamic Philosophy and the Spiritual Awakening of Islam - Muhammad Rasyid Ridlo; Shofiyullah Muzammil (al-Afkar, Journal For Islamic Studies, 2026)
Muhammad Iqbal offered the concept of khudi as a solution to the intellectual and spiritual stagnation of Muslims due to the dominance of Western civilization. Khudi, which means ego or the self, aims to strengthen individual consciousness and collective transformation towards the spiritual revival of Islam. This research uses the literature method, which examines Iqbal's thoughts in a descriptive-narrative manner. The results show that khudi is the main motor of revival, which rejects fatalism, integrates Islamic values and modernity and fights colonialism. Khudi became a tool to build an independent, creative and dynamic society. However, its application in the modern context requires further research to answer the complex challenges of the contemporary world.